2021
DOI: 10.3390/biomedicines9060662
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Reverse Transcriptase Increases Proliferation and Lifespan of Human NK Cells without Immortalization

Abstract: NK cells are the first line of defense against viruses and malignant cells, and their natural functionality makes these cells a promising candidate for cancer cell therapy. The genetic modifications of NK cells, allowing them to overcome some of their inherent limitations, such as low proliferative potential, can enable their use as a therapeutic product. We demonstrate that hTERT-engineered NK cell cultures maintain a high percentage of cells in the S/G2 phase for an extended time after transduction, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…As a result, NK cells may address the limitations of autologous CAR T cell therapy. However, there are several potential drawbacks to the usage of NK cells, such as difficulty in cell culture, immediacy in the peak activity of cellular kinetics, and shorter intrinsic longevity as well as limited memory phenotype in the life span and response [ 34 , 37 , 38 ]. Other research involves combinational therapies using DC or T cells and immune checkpoint inhibitors such as anti-PD1 (programmed cell death protein1) [ 39 ] or anti-PD-L1 (programmed death-ligand1) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, NK cells may address the limitations of autologous CAR T cell therapy. However, there are several potential drawbacks to the usage of NK cells, such as difficulty in cell culture, immediacy in the peak activity of cellular kinetics, and shorter intrinsic longevity as well as limited memory phenotype in the life span and response [ 34 , 37 , 38 ]. Other research involves combinational therapies using DC or T cells and immune checkpoint inhibitors such as anti-PD1 (programmed cell death protein1) [ 39 ] or anti-PD-L1 (programmed death-ligand1) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, transfected NK cells were not able to grow autonomously in nonobese diabetic severe‐combined‐immunodeficient γc−/− (NSG) mice and still eventually developed delayed senescence in vitro ( 147 ). More recently, Streltsova and coworkers corroborated that stable hTERT ectopic expression, even when gamma-retrovirus is used, increases the proliferation and lifespan of expanded and activated (K562-mbIL21+IL2) NK cells rather than complete immortalization ( 168 ). The safety of this strategy is a critical question because so far, the inability of ectopically expressed hTERT to cause oncogenic transformation of NK cells has not been firmly established.…”
Section: Surmounting Replicative Senescence: ‘Buying Time’ For Nk Cel...mentioning
confidence: 99%
“…A number of studies have shown that cells with an increased level of TERT have greater resistance to external damaging factors and are more protected from cell death [ 8 , 33 , 35 , 41 , 49 , 50 , 52 , 77 , 107 ]. Such stability, according to recent data, is due not only to the intranuclear activity of TERT (lengthening of telomeric ends and regulation of gene expression), but also due to the its cytoplasmic function: cell death regulation through direct interaction with mitochondria and proteins of the apoptotic pathway.…”
Section: The Role Of Tert In the Regulation Of Apoptosis In The Cytop...mentioning
confidence: 99%
“…Immune cells transferred into a recipient were found to rapidly downregulate their activity despite their accumulation within tumor sites [ 153 ]. It was shown that TERT overexpression in modified T [ 154 ] and NK cells [ 107 , 155 ] increases their replicative potential and overall functional activity after long-lasting cultivation. This approach might help to overcome the development of immunosuppression during cancer treatment [ 156 , 157 , 158 ].…”
Section: Therapeutic Approaches To Cure Cancermentioning
confidence: 99%